THE TYPOLOGY OF TRAVELS IN PRISTINA IN RELATION TO PURPOSE, TIME AND DISTANCE - Humolli, Fitim; Çinaj, Nevila; Kelmendi, Naim (Quaestiones Geographicae, 2020)
Similar to most cities in Europe/the world, Kosovo also faces the problem of urban mobility, which is characterised by congestion. The most concerning problems are: waste of time, money, energy consumption, environmental problems and others. They arise due to the imbalanced state of using urban mobility in Pristina (Prishtinë), while eco-travels are minor. In order to reduce these problems, this paper aimed to examine the current situation of urban mobility in Pristina by analysing the mobility indicators of cars, trains, buses, bicycles and walking, in relation to purpose, distance and time. The research methodology was the direct survey method conducted with the citizens of Pristina and daily immigrants over a week. The results of the survey showed that 44% of the participants used cars for travelling, while other transportation alternatives (soft and eco-transport) were limited and problematic. In the absence of institutional practices for collecting periodic data, the results of this study will not only contribute in filling the information gap, but also will properly address the needs for transportation planning in Pristina and design objectives for a multimodal transportation strategy in this city to lessen the negative impacts of the aforementioned problems and increase travel facilities.